10 Years of Nephrogenic Systemic Fibrosis: A Comprehensive Analysis of Nephrogenic Systemic Fibrosis Reports Received by a Pharmaceutical Company from 2006 to 2016. Issue 9 (September 2018) - Endrikat, Jan; Dohanish, Susan; Schleyer, Nicolas; Schwenke, Susanne; Agarwal, Sheela; Balzer, Thomas
Abstract : Objectives: The aim of this study was to critically assess the evaluation and categorization process for nephrogenic systemic fibrosis (NSF) based on reports received by Bayer from 2006 to 2016. Materials and Methods: A total of 779 NSF reports received by Bayer globally from 2006 to 2016 were included in the analysis. Arlington Medical Resources provided gadolinium-based contrast agent (GBCA) market share. Reports were conservatively categorized based on the Cowper/Girardi criteria. A statistical model simulated the impact of market share and market introduction on the number of unconfounded reports. Results: For all reports, reported onset of disease ranged from 1996 and 2012. Of 779 reports, 325 involved a Bayer product only, 208 involved only products from other companies (or unknown GBCA), and 246 involved both Bayer and non-Bayer products. Most of all reports (86%) originated from the United States. Through 2006, Magnevist and Omniscan dominated the US market (>80% combined market share). All other GBCAs with fewer NSF reports comprised the remaining combined market share of less than 20% or were introduced after May 2007, after safety recommendations came into effect. A total of 563 reports (220 single-agent and 343 multiagent reports) involved Magnevist. In at least 150 of the 343 reports, a different GBCA (Omniscan, 118; OptiMARK, 15; MultiHance, 6; and macrocyclic agent, 11) showed the closest temporal relationship to onset of NSF-like symptoms. The simulation model demonstrated that patients receiving a GBCA with lower market share and late market introduction are less likely to be observed in an unconfounded setting. Conclusions: Year of market introduction, as well as US market share in 2000 to 2007, greatly influenced the absolute number of NSF reports for each GBCA, their a priori probability to cause NSF, as well as their a priori probability to be associated with unconfounded cases of NSF. Variability in case interpretation and pharmacovigilance approaches also influence the absolute number of unconfounded cases and should therefore not be used for comparative risk assessments. This should be primarily based on objective product parameters such as structure, stability, pharmacokinetics, and dose.